Pengaruh Penggunaan Media Papan Kerak Berbantuan Model Problem Based Learning dalam Meningkatkan Hasil Belajar pada Materi Sistem Pencernaan Manusia Kelas VB SDK 143 Bhaktyarsa - Anastasia Imelda; Maria Herliyani Dua Bunga; Yohanes Ehe Lawotan (Journal on Education, 2023)
This study aimed to determine the effect of using the crust board media assisted by the problem-based learning (PBL) model on student learning outcomes. This study used experimental quantitative research method with a one-group pre-test-post-tes research design. The sample used in this study was 20 people. Data collection techniques in this study used tests, observation and documentation. Data analysis techniques were using normality test and hypothesis testing. The result revealed that the average posttest score of student improved after using the problem-based learning (PBL) model-assisted crust board media compared to the average pretest score. The data analysis technique used a hypothesis test(t-tes) with the help of the SPSS version 25 program. The results showed a ttable of 1.725 and a tcount of 5.583 then the results of tcount were consulted with ttable foer one group test, where ttable (N=20) because tcount > ttable means the results of the two samples weresignificantly different. Thus it can be concluded that, there was a significant difference between the results of the pre-test and post-test which showh that the alternative hypothesis proposed by the researcher was accepted that also indicated that there was an effect of using crust board media assisted by the problem-based learning (PBL) model in improving learning outcomes on human digestive system the material at grade VB SDK 143 Bhaktyarsa. Based on the research findings, it can be concluded that there was an effect of using the PBL model-assisted crust board media in improving learning outcomes on human digestive system material at grade VB SDK 143 Bhaktyarsa